Die betörenden Worte des fremden Mannes: Zur Funktion der Paulusbeschreibung in den Theklaakten - Betz, Monika (New Testament studies, 2007)
The Acts of Thecla develop a narrative Christian counter-world to their pagan society. In this context erotic motifs are adapted and re-interpreted. It is into this framework that the description of the Apostle Paul is to be placed. In his human appearance he proves to be the antitype of the erotic lover such as depicted in the stereotypes of Greco-Roman novels. When Thecla, however, feels irresistibly attracted to him, it is his function as the mediator of Christ that attracts. Thus, Thecla's conversion to Christian faith is presented as a special act of falling in love with the Gospel.